Smile circus: reducing anxiety with dental clowning techniques - Aggarwal, Charu; Gupta, Sonal; Shrivastava, Rohan; Abraham, Nayana; Subramanian Shanthi, Akil Prawin (International Journal of Contemporary Pediatrics, 2025)
Dental anxiety among children is a universal challenge, often creating barriers to effective treatment and fostering long-term fear of oral care. Smile Circus introduces the extraordinary world of dental clowning, an innovative approach that transforms dental clinics into spaces of joy and laughter. Through the clever use of humor, role-play and storytelling, dental clowns ease anxiety and build trust with young patients, making the scary dental visit an adventure rather than a challenge. Techniques like whimsical theatrics, playful interactions with dental tools and imaginative games turn fear into fascination. This article deals with the mechanisms behind dental clowning's success, highlighting its ability to cultivate positive associations with dentistry. The findings reveal a promising model where emotional well-being aligns harmoniously with oral health, paving the way for happier, healthier paediatric patients. With dental clowning, smiles extend beyond treatments, proving that laughter truly is the best medicine in paediatric dentistry.